PROFIL MOTIVASI BELAJAR DALAM IMPLEMENTASI ICE BREAKING di KELAS IV SD ISLAM ALMADINA SEMARANG - Tarisa Tarisa; Joko Siswanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to describe the profile of learning motivation in the implementation of ice breaking in class IV of Almadina Islamic Elementary School, Semarang. This research use desciptive qualitative approach. The resource persons for this research were teachers and fourth grade students. The techniques for collecting data in this research are interviews, observation and documentation. Data analysis uses data reduction techniques, data presentation, and drawing conclusions. The results of the research show that the learning motivation profile is the learning motivation profile in the implementation of ice breaking in class IV of Almadina Islamic Elementary School, Semarang. During each break in the learning process, ice breaking activities are usually used, namely using variations of clapping, asking about news, variations of games or games. Learning motivation can be increased by implementing ice breaking activities for fourth grade students at Al Madina Islamic Elementary School Semarang, the impact of which is that students concentrate on the entire learning process and understand that ice breaking can dilute the atmosphere which was previously less conducive to become more conducive